Inhibition of ESCRT-independent extracellular vesicles biogenesis suppresses enterovirus 71 replication and pathogenesis in mice - Liang, Yicong; Kong, Yue; Rao, Menglan; Zhou, Xing; Li, Chengcheng; Meng, Yi; Chen, Yanxi; Li, Hongjian; Luo, Zhen (International journal of biological macromolecules, 2024)
Enterovirus 71 (EV71) causes hand-foot-and-mouth disease (HFMD), neurological complications, and even fatalities in infants. Clinically, the increase of extracellular vesicles (EVs) in EV71 patients' serum was highly associated with the severity of HFMD. EV71 boosts EVs biogenesis in an endosomal sorting complex required for transport (ESCRT)-dependent manner to facilitate viral replication. Yet, the impact of EVs-derived from ESCRT-independent pathway on EV71 replication and pathogenesis is highly concerned. Here, we assessed the effects of EV71-induced EVs from ESCRT-independent pathway on viral replication and pathogenesis by GW4869, a neutral sphingomyelinase inhibitor. Detailly, in EV71-infected mice, blockade of the biogenesis of tissue-derived EVs in the presence of GW4869 restored body weight loss, attenuated clinical scores, and improved survival rates. Furthermore, GW4869 dampens EVs biogenesis to reduce viral load and pathogenesis in multiple tissues of EV71-infected mice. Consistently, GW4869 treatment in a human intestinal epithelial HT29 cells decreased the biogenesis of EVs, in which the progeny EV71 particle was cloaked, leading to the reduction of viral infection and replication. Collectively, GW4869 inhibits EV71-induced EVs in an ESCRT-independent pathway and ultimately suppresses EV71 replication and pathogenesis. Our study provides a novel strategy for the development of therapeutic agents in the treatment for EV71-associated HFMD.